Development of the Invariant Modeling Method for Management of the Phase Structure of the Welded Materials under Low Arctic Temperatures - Krektuleva R. A.; Saraev Yu. N.; Perovskaya M. V.; Semenchuk V. M.; Sigagin M. M.; Cherepanov R. O. Roman Olegovich; Cherepanov O. I. (2018, 2018)
Title screen